2007
DOI: 10.1007/s10278-007-9048-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Breast Attenuation in Patients Undergoing Myocardial Perfusion Scintigraphy: A Digital X-Ray Study

Abstract: Attenuation artifacts are the most common sources of error in myocardial single-photon emission computed tomography (SPECT) imaging. Breast artifacts are the most frequent causes of false positive planar images in female subjects. The purpose of this study was to predict breast adverse attenuation by measuring breast tissue thickness with digital x-ray. Sixty-five consecutive female patients with angina pectoris, who were referred to myocardial perfusion scintigraphy were enrolled in this study. Eighteen patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…According to Yardi and Bruckman [ 18 ], ICT-Work is important to prepare and motivate students for future work performance. Numerous studies have found that engineering graduates are unable to meet the requirements of the corporate world (e.g., OECD [ 4 ]; Saad and Majid [ 19 ]; Winberg, et al [ 20 ]), as they lack ICT skills and competencies at an advanced level [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Yardi and Bruckman [ 18 ], ICT-Work is important to prepare and motivate students for future work performance. Numerous studies have found that engineering graduates are unable to meet the requirements of the corporate world (e.g., OECD [ 4 ]; Saad and Majid [ 19 ]; Winberg, et al [ 20 ]), as they lack ICT skills and competencies at an advanced level [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%